Assessment The Method of Fuzzy Logic to Determine The Quality of Service Expedition in Jabodetabek Area - Pamuji, Agus (Scientific Journal of Informatics, 2016)
Search application services that was designed, could be the based on the difficulty to find out, and to select expedition services which have provided. In these case, when someone who wants to send the packages to a particular destination. Each shipper will see the name of courier services, the speed the god arrive at the destination, prices, and customer services. This application is designed with fuzzy logic method that can be based on the selection of criteria, and specific category. The using and fuzzy logic method implementation can to help and ensure the selection of expedition service that based in variable or criteria are price, speed, location, and services. The result of this research will to display of application that was supported with database systems such as expedition services information and location, and then table of price is available.